NUTRIENT UPTAKE OF RABI PIGEON PEA (Cajanus cajan (L) Millsp) AS INFLUENCED BY DIFFERENT NUTRIGATION LEVELS - V. RAMULU, P. CHANDRA SEKHAR, K. AVIL KUMAR, M. UMA DEVI and (The Journal of Research, PJTSAU, 2017)
Pigeonpea (Cajanus cajan Millsp.) is an important crop amongst pulses. It plays a major role in the house hold economy of farmers by providing protein rich food, firewood and income to the resource poor small/marginal farmers in tropics and subtropics and has long been recognized for its attributes of high leaf fall and conseque nt contribution to the carbon and nitrogen economy of the soil (Rego and Rao, 2000). Pigeonpea grown during rabi season with limited irrigation water though drip system resulted in increased yield (Mahalakshmi et al.,2011). Nutrient uptake plays a significant role in deciding the pigeonpea yield and by knowing the level of nutrient accumulation in the crop helps in the formulating the efficient fertilization schedule, as most of the applied nutrients are lost through leaching, volatilization, denitrification and chemical fixation in soil. Practically very limited information is available on uptake of nutrients by pigeonpea crop grown with variable levels of recommended dose of fertilizers under drip nutrigation. So it has been considered worthwhile to study the uptake of nutrients in pigeonpea as affected by different nutrigation levels.